Healthcare influencers: Analysis of the role of Spanish healthcare professionals in social networks - Matarín Rodríguez-Peral, Eva; Gómez Franco, Tomás; Fondón Ludeña, Anabell (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This study analyses the main Spanish health communicators who interact with Twitter. It studies the main topics they deal with, as well as the structure of their network of interrelationships. Ten profiles of health professionals with more than 12,500 followers and a network with 797 nodes and 1562 edges have been analysed. The network analysis was carried out by studying the centrality through various algorithms and elaborating graphs using the Gephi programme. The health influencers with the greatest weight in the network were determined. The modularity analysis resulted in the identification of 15 influencer communities.